2018
DOI: 10.1002/rsa.20834
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of large Boltzmann outerplanar maps

Abstract: We study the phase diagram of random outerplanar maps sampled according to nonnegative Boltzmann weights that are assigned to each face of a map. We prove that for certain choices of weights the map looks like a rescaled version of its boundary when its number of vertices tends to infinity. The Boltzmann outerplanar maps are then shown to converge in the Gromov-Hausdorff sense towards the -stable looptree introduced by Curien and Kortchemski (2014), with the parameter depending on the specific weight-sequence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Second, it is often challenging to relax an assumption involving a finite exponential moment condition to a finite variance condition: in particular, the proof of Theorem 1.2 uses different techniques than in [17,Theorem 13], and new ideas. We emphasize that until now, convergence towards the Brownian CRT of similar rescaled discrete weighted tree-like structures has mostly been obtained under finite exponential moment conditions (see [17,Theorems 1,13 and 14], [48,Theorem 5.1], [53,Theorem 6.60], and in particular the discussion in [51,Section 3.3]). Third, the method is robust, as it allows to treat the case σ 2 µ = ∞, which was left as an open question in [18].…”
Section: Scaling Limits Of Looptrees (Crt Regime)mentioning
confidence: 99%
“…Second, it is often challenging to relax an assumption involving a finite exponential moment condition to a finite variance condition: in particular, the proof of Theorem 1.2 uses different techniques than in [17,Theorem 13], and new ideas. We emphasize that until now, convergence towards the Brownian CRT of similar rescaled discrete weighted tree-like structures has mostly been obtained under finite exponential moment conditions (see [17,Theorems 1,13 and 14], [48,Theorem 5.1], [53,Theorem 6.60], and in particular the discussion in [51,Section 3.3]). Third, the method is robust, as it allows to treat the case σ 2 µ = ∞, which was left as an open question in [18].…”
Section: Scaling Limits Of Looptrees (Crt Regime)mentioning
confidence: 99%
“…For example, the same authors showed in [CK15] that a stable looptree arises as the scaling limit of the boundary of a critical percolation cluster on the UIPT, and Richier showed in [Ric18a] that the incipient infinite cluster of the UIHPT has the form of an infinite discrete looptree. Further results along these lines can be found in [CK15], [CDKM15], [SS19], [BR18], [CR18] and [KR], though this is a very non-exhaustive list. More generally, they also arise as the scaling limits of boundaries of stable maps [Ric18b], and are emerging as an important tool in the programme to reconcile the theories of random planar maps and Liouville quantum gravity, demonstrated for example in [MS15], [GP] and [BHS18].…”
Section: Introductionmentioning
confidence: 99%
“…Second, further studies of different weight sequences may lead to the discovery of new phenomena. Contemporary examples include the α-stable maps by Le Gall and Miermont [38] and limit theorems for face-weighted outerplanar maps in [45].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%